1962
DOI: 10.1103/physrevlett.9.509
|View full text |Cite
|
Sign up to set email alerts
|

npElastic Charge Exchange in the BeV Energy Region

Abstract: DECEMBER 15, 1962 (1962)] or in the K ~K system [S. Minami, Progr. Theoret. Phys. (Kyoto) 27, 215(1962)]. 5 If the Z particle is regarded as a bound state in the N -N system, it would then correspond to the 3 3 P 0 state.For an explanation of the notation, see the first paper cited in reference 4. 6 Another possible reaction mechanism is one in which the incident K~ meson interacts directly with the nucleon and a K meson is produced through a Yukawa-type interaction without any KK interaction.The n-p elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1964
1964
1975
1975

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Preliminary reports [1][2][3] of this work have been published elsewhere. Previous experiments [4][5][6][7][8][9][10][11][12] indicated that this process has several interesting characteristics. There is a peak in the angular distributions which is much sharper than the peak in p-p scattering.…”
Section: N+p~p+nmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary reports [1][2][3] of this work have been published elsewhere. Previous experiments [4][5][6][7][8][9][10][11][12] indicated that this process has several interesting characteristics. There is a peak in the angular distributions which is much sharper than the peak in p-p scattering.…”
Section: N+p~p+nmentioning
confidence: 99%
“…The general shape of the cross section at 3 GeV/c [4,5] can be described by da/dt = A e -Bltl + C e -DIrl ,…”
Section: N+p~p+nmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Byers 10 also calculated the high-energy n-p backward cross section using the coherent-droplet model with an OPE term dominating for large impact parameter.…”
Section: The High Partial Waves Contribute Significantly To/3 Since mentioning
confidence: 99%
“…5 These features of the cross section suggest that the long-range part of the interaction, hence, the small-angle cross section, is associated with the exchange of a single pion. The 5-channel helicity amplitudes M(\p', ^n> ^n>^p) f°r t nis process are given in Born approximation for single pion exchange by …”
mentioning
confidence: 99%